2023
DOI: 10.3390/ma16031187
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Kinetics of Ti-6Al-4V Alloys by Conventional and Electron Beam Additive Manufacturing

Abstract: New manufacturing processes for metal parts such as additive manufacturing (AM) provide a technological development for the aeronautical and aerospace industries, since these AM processes are a means to reduce the weight of the parts, which generate cost savings. AM techniques such as Laser Powder Bed Fusions (LPBF) and Electron Beam Fusion (EBM), provided an improvement in mechanical properties, corrosion resistance, and thermal stability at temperatures below 400 °C, in comparison to conventional methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…However, the surface microhardness value of the Ti6Al4V-1.0 wt.% Y 2 O 3 alloy increases until 800 °C and then decreases at 1000 °C, which can be explained by the competition mechanism. The change in microhardness is mainly attributed to the heterogeneity quality and the oxide surface layer hardening occurring [ 7 ], which is also affected by the increase in the oxidation temperature and the diffusion of oxygen from the outside of the oxide layer [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the surface microhardness value of the Ti6Al4V-1.0 wt.% Y 2 O 3 alloy increases until 800 °C and then decreases at 1000 °C, which can be explained by the competition mechanism. The change in microhardness is mainly attributed to the heterogeneity quality and the oxide surface layer hardening occurring [ 7 ], which is also affected by the increase in the oxidation temperature and the diffusion of oxygen from the outside of the oxide layer [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, oxygen diffusing inwards dominates the growth of the oxide layer, which is also affected by the dense layer causing a slow oxidation rate [18]. For traditional oxidation, it is relatively fast before the oxide layer forms at the beginning, and then thermal oxidation slows down, as atoms need to diffuse through the oxide layer (Figures 4 and 7) [19,20].…”
Section: Oxidation Mechanism Of Titanium With Vanadiummentioning
confidence: 99%
“…The authors reported that the passive layer is homogenous when passivate is generated in pure titanium (Ti CP2 or any CP). However, when the passivation is created in titanium alloy, the passive layer can be heterogeneous due to the difference in alloying elements; adding a small oxide layer can be a problem due to the penetration of different ions (Cl − , OH − or SO 2 2− ) in the surface by interstitial mechanisms [16][17][18][19][20]. Other options to protect titanium are plasma electrolytic oxidation (PEO) and sol-gel coatings; those techniques require special equipment to generate the layer, and the cost and difficulty of coating increase in some geometries [21,22].…”
Section: Introductionmentioning
confidence: 99%